2021
DOI: 10.1186/s12935-021-01857-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a novel glycolysis-related gene expression signature for gastrointestinal cancer in the Asian population

Abstract: Background Globally, gastrointestinal (GI) cancer is one of the most prevalent malignant tumors. However, studies have not established glycolysis-related gene signatures that can be used to construct accurate prognostic models for GI cancers in the Asian population. Herein, we aimed at establishing a novel glycolysis-related gene expression signature to predict the prognosis of GI cancers. Methods First, we evaluated the mRNA expression profiles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Selenophosphate synthetase 1 (SEPHS1) promotes the expression of SMADs in liver cancer cells and stimulates the migration and invasion of tumors induced by TGF-β, which is negatively correlated with the OS and RFS of HCC patients ( Yang et al, 2021 ). Glucosamine-6-phosphate deaminase 1 (GNPDA1) and procollagen-lysine (PLOD2) are upregulated in liver cancer and promote tumor proliferation and migration, which are correlated with poor prognosis ( Du et al, 2017 ; Xia et al, 2021 ). Mutation of Beta-1, 4-galactosyltransferase 2 (B4GALT2) leads to abnormal glycosylation of proteins, promoting the development of colon cancer ( Venkitachalam et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selenophosphate synthetase 1 (SEPHS1) promotes the expression of SMADs in liver cancer cells and stimulates the migration and invasion of tumors induced by TGF-β, which is negatively correlated with the OS and RFS of HCC patients ( Yang et al, 2021 ). Glucosamine-6-phosphate deaminase 1 (GNPDA1) and procollagen-lysine (PLOD2) are upregulated in liver cancer and promote tumor proliferation and migration, which are correlated with poor prognosis ( Du et al, 2017 ; Xia et al, 2021 ). Mutation of Beta-1, 4-galactosyltransferase 2 (B4GALT2) leads to abnormal glycosylation of proteins, promoting the development of colon cancer ( Venkitachalam et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPD1 encodes glycerol-3phosphate dehydrogenase 1 (GPD1), which played a pivotal role in lipid metabolism through catalyzing the transformation of NADH and dihydroxyacetone phosphate to NAD+ and glycerol-3-phosphate reversibly (Yoneten et al, 2019). Studies suggested that GPD1 was closely related to prognosis of gastrointestinal cancer, breast cancer, and glioblastoma (Xie et al, 2020;Xia et al, 2021). Survival analysis revealed that no matter in the training cohort or the verification cohort, the established risk model exhibited potent predictive performance for the survival of osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the 5-year overall survival rate after gastric cancer in China was approximately 20% [ 3 ], whereas that of colorectal cancer was 60% [ 4 ]. Consequently, accurate markers for therapy response are required to improve the prognosis of GI cancer patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%